Modes de vie et environnement - Salvador Juan (VertigO)
Many authors consider the change of ways of life, towards more “sustainability”, as an essential condition for ecological transition. But a clear definition of the term ways of life, often confused with the word lifestyle, is never given. However, the distinction between these terms is important for understanding the various constraints that rigidify daily life and lead to the ineffectiveness of ecological reform projects for consumption and ordinary uses. This paper explains why, and shows that the level of analysis of the kinds of life would allow a better targeted public action at the categorical level and therefore an ecological change of practices more socially acceptable.